Hereditary neurodegenerative disorders with spastic-ataxic manifestations: genetic and clinical insights into previously reported variants - Riaz Ahmad; Kanwal Ayaz; Misbah Naeem Khan; Muhammad Naeem; Henry Houlden (Neurogenetics, 2026)
Abstract Hereditary neurodegenerative disorders comprise a heterogeneous group of genetic conditions that affect the central and/or peripheral nervous system, often presenting with hallmark clinical features including ataxia, spasticity, dystonia and neuropathy. Our study aims to investigate the underlying cause of rare and overlapping phenotypes of inherited neurodegenerative disorders in the four familial cases of the Pakistani population. Four Pakistani families with a wide range of spastic-ataxic features were evaluated using exome sequencing, homozygosity mapping, and Sanger sequencing. These molecular studies identified four known pathogenic variants: CYP2U1 :c.604G > A (p.Glu202Lys), ATXN1 expansion: [(CAG)46/(CAG)27], ATM :c.103 C > T (p.Arg35*), and COQ4 :c.577 C > T (p.Pro193Ser). All these phenotypes were correlated with the literature-based reported cases of rare neurological disorders. We present previously reported pathogenic variants in our enrolled 13 affected individuals from four unrelated families. Our findings underscore the pathogenic relevance of the identified variants and pinpoint their importance for regional diagnostic and genetic counseling strategies.